A physical model for the characterization of magnetic hydrogels subject to external magnetic fields - Madeo, Dario; Bevilacqua, Giuseppe; Biancalana, Valerio; Dancheva, Yordanka; Mocenni, Chiara (Journal of magnetism and magnetic materials, 2020)
•A 2D microscopical scalable physical model for magnetic hydrogels is proposed.•Free response of the system is similar to an harmonic oscillator with reduced mass.•Characterization of hydrogels response to external magnetic field.•System geometry and temperature are changed for specific frequencies of the external field. Magnetic hydrogels are interesting nanomaterials able to change their shape and temperature if exposed to external magnetic fields. Thanks to these features, which originate from the microstructure of magnetic hydrogels (magnetic nanoparticles tied together through polymeric chains), these substances have several applications in technological fields and biomedicine. Hydrogels are able to absorb and release large amounts of water, which makes them eligible materials for drug delivery. This feature is made even more attractive in cases where the delivery/release can be externally controlled. Controlling the system using external magnetic fields requires keystone processes like modeling and simulation. In this paper, the properties of the system have been analyzed using a 2D microscopical simulation of a suitable physical model. Experimentally, the behavior of the system with and without the application of external magnetic fields and its dissipative effects have been characterized. Specifically, we analyze the change of size and temperature of an hydrogel system as a function of the external magnetic field frequency, thus providing a fundamental tool for developing magnetic substances suitable for specific applications.